GERMPLASM POTENTIAL FOR DIFFERENT ADVANCE LINES OF GOSSYPIUM HIRSUTUM FOR WITHIN BOLL YIELD COMPONENTS - SHAFIQUE, MT; BANO, M; KHALID, MN; RAZA, A; SHAHID, M; HUSSNAIN, H; IQBAL, M; HUSSAIN, M; ABBAS, Q; IQBAL, MM; et al. (Biological and Clinical Sciences Research Journal, 2023)
Cotton production per hectare is low in Pakistan due to many biotic and abiotic factors. As boll is the basic determinant for yield in cotton crop, a study on within boll yield parameters was carried out using 24 cotton bulk and 2 check varieties to check their variability for within boll yield components. The experiment was performed in the research area of ​​the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad. The genotypes were seeded in two replications following a randomized complete block design. Data were subjected to analysis of variance to check significance among different genotypes. Genotypes were significantly different. The genotype PB-132 performed best for most parameters including GOT, lint index, lint mass per seed, and seed density. Correlation analysis was applied to find out the association of these parameters. Seed cotton yield was positively associated with the GOT, boll weight and number of seeds per boll while it negatively correlated with fiber fineness, seed volume, and seed surface area. The first principal component showed 26.37%, the second component showed 17.93%, the third component showed 14.88%, and the fourth component showed 14.40% of total variation. PCA analysis showed the genetic diversity among cotton genotypes. The current study's findings revealed the potential of different bulks of cotton for developing high-yielding varieties. This information may be used to develop breeding strategies to enhance cotton production and variety.